1998
DOI: 10.1097/00042560-199811010-00010
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends in HIV Risk Behaviors of Out-of-Treatment Injection Drug Users and Injection Drug Users Who Smoke Crack

Abstract: This study compared the baseline sociodemographic characteristics and HIV risk behaviors of two groups of out-of-treatment injection drug users (IDUs): 366 who concurrently smoked crack (smoking IDUs) and 212 who did not smoke crack (IDUs) in the past 30 days. Temporal trends in recent risk behaviors were also assessed for each drug user group over an 18-month period, January 1992 through June 1994. Baseline data were collected in South Philadelphia before the implementation of a multisite HIV intervention res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…It is possible that periodic assessments of HIV risk behaviors could be a marker of quality of substance abuse treatment used in the accreditation process of substance abuse treatment programs. Although we saw no relationship between substance use treatment exposure and HIV risk behaviors, consistent with other studies (Booth et al, 2000;Fuller et al, 2002;Latkin, Mandell, & Vlahov, 1996;Logan & Leukefeld, 2000;Rasch et al, 2000;Roy et al, 2003;Semaan et al, 1998;Tortu et al, 2000), we did find that younger age and cocaine use were associated with higher sexual risk behaviors, suggesting the need to target intervention efforts to these groups in particular. Notably, our findings demonstrated lower rates of HIV-related drug use risk among Blacks; these findings are surprising as previous study indicates higher injection drug use rates (Turner, Miller, & Moses, 1989) and related HIV risk (Kottiri, Friedman, Neaigus, Curtis, & Des Jarlais, 2002;CDC, 2002) among Blacks as compared with Whites.…”
Section: Discussionsupporting
confidence: 89%
“…It is possible that periodic assessments of HIV risk behaviors could be a marker of quality of substance abuse treatment used in the accreditation process of substance abuse treatment programs. Although we saw no relationship between substance use treatment exposure and HIV risk behaviors, consistent with other studies (Booth et al, 2000;Fuller et al, 2002;Latkin, Mandell, & Vlahov, 1996;Logan & Leukefeld, 2000;Rasch et al, 2000;Roy et al, 2003;Semaan et al, 1998;Tortu et al, 2000), we did find that younger age and cocaine use were associated with higher sexual risk behaviors, suggesting the need to target intervention efforts to these groups in particular. Notably, our findings demonstrated lower rates of HIV-related drug use risk among Blacks; these findings are surprising as previous study indicates higher injection drug use rates (Turner, Miller, & Moses, 1989) and related HIV risk (Kottiri, Friedman, Neaigus, Curtis, & Des Jarlais, 2002;CDC, 2002) among Blacks as compared with Whites.…”
Section: Discussionsupporting
confidence: 89%
“…doi:10.1016/j.jsat.2005.08.008 injection drug-using sexual partners who are at higher risk of having HIV (National Center for HIV, STD and TB Prevention, 2002b). Although studies have shown that HIV risk related to drug use behavior has declined among people who use a variety of drugs, whether in or out of drug treatment settings, sexual behavior in this population remains an important source of HIV risk (Battjes, Pickens, & Brown, 1995;Semaan et al, 1998;Strathdee & Sherman, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated an association between crack cocaine use and high rates of infection with HIV and other STIs, especially among injecting drug users who are exposed to both parenteral and sexual risks [8,[12][13][14][15][16][17][18][19]. Other studies have shown that female crack cocaine users engage in risky sexual behaviors that increase the risk of contracting STIs (e.g.…”
mentioning
confidence: 99%